2019
DOI: 10.1109/tbme.2019.2950777
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation Pattern Efficiency in Percutaneous Auricular Vagus Nerve Stimulation: Experimental versus Numerical data

Abstract: Percutaneous electrical stimulation of the auricular vagus nerve (pVNS) is an electroceutical technology. The selection of stimulation patterns is empirical, which may lead to under-stimulation or over-stimulation. The objective is to assess the efficiency of different stimulation patterns with respect to individual perception and to compare it with numerical data based on in-silico ear models. Methods: Monophasic (MS), biphasic (BS) and triphasic stimulation (TS) patterns were tested in volunteers. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…Inspection and analysis of the activation of axons for these pulse types indeed showed that due to the relatively long phase duration of 0.3 ms, excitation was either induced by the anodal or the cathodal phase and was in most cases independent of the order of the two phases, yielding similar excitation thresholds. This is in accordance with [30] stating that dependency on the order of the phases is only given for short phase durations, in the order of 100 µs. Comparing biphasic pulses with anodal monophasic pulses (e.g.…”
Section: B Maximum Diameter Specificitysupporting
confidence: 92%
See 2 more Smart Citations
“…Inspection and analysis of the activation of axons for these pulse types indeed showed that due to the relatively long phase duration of 0.3 ms, excitation was either induced by the anodal or the cathodal phase and was in most cases independent of the order of the two phases, yielding similar excitation thresholds. This is in accordance with [30] stating that dependency on the order of the phases is only given for short phase durations, in the order of 100 µs. Comparing biphasic pulses with anodal monophasic pulses (e.g.…”
Section: B Maximum Diameter Specificitysupporting
confidence: 92%
“…The results can be validated by comparison with literature describing both experimental and numerical studies, however, a complete validation of all parameter ranges would not be practically achievable with human subjects due to the large number investigated cases. A recent experimental and numerical pVNS study [30] investigated activation of Aβfibers (8.3 µm) and Aδ-fibers (3.5 µm) for an 'individual numerical model' and a 'simple numerical model', of which the latter corresponds well to this model.…”
Section: Validation and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, biphasic waveforms have been lately proposed since they can lead to larger recruitment of nerve fibers compared to monophasic waveforms (Kaniusas et al, 2019a). Monophasic, biphasic and triphasic stimulation patterns for different bursts lengths were recently compared (Kaniusas et al, 2020). This aspect of being able to manipulate the waveform, therefore, may allow us to tailor the strength of our stimulation depending on the specific disease condition.…”
Section: Toward Circuit-based Tvns: Translational Approachesmentioning
confidence: 99%
“…The main challenges in the optimization of the auricular VNS are the precise targeting of aVN in the external ear and the selection of proper stimulation parameters to recruit aVN fibers close to the stimulation electrodes (Kaniusas et al, 2019c). The anatomical map of external ear innervation can address the FIGURE 6 | Inter-centroid distance and minimum distance between nerves and arteries within each slide (blue squares denote outliers).…”
Section: Discussionmentioning
confidence: 99%